PERUSAHAAN KECIL DENGAN PERTUMBUHAN TINGGI: PERSPEKTIF KEBIJAKAN PUBLIK - Didin Muhafidin (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2019)
This study aims to find out whether there are signs that public policy is beginning to understand that it is not only in startup companies that can achieve high levels of growth. More research is needed to find out what company needs are more mature, before policies move away from supporting early stage companies. In examining the implications of recent research on small companies with a large impact, we must resist the temptation to rule out useful programs that support early-stage business.